Bermain Sebagai Media Untuk Mengubah Sikap Pemalu pada Anak Prasekolah - Yuarini Wahyu Pertiwi (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2023)
Shyness in children affects the child's ability to adapt in social environment and cannot maximize his abilities at school, so it is necessary to provide psychological intervention with playing as a media. This is because playing is the biggest activity in a child's world, and one of the way for children talk or express their feelings to others. The games that will be giver are active play such as constructive games, role plays, sports games and group play. The aim of this research is to determine the success of the intervention provided. The research method used is a qualitative case study with 1 respondent. Before the intervention process, researchers collected data through interviews, observations and psychological tests from respondents. Based on the data, the results of this research show that respondents have not actualized their abilities optimally and tend to close themselves off and withdraw from the environment. The results of the intervention show that individuals are more confident, have better interactions, a desire to play with friends, have better social skills, have the courage to express their feelings, and are more active in school activities. Thus it is concluded that playing can be a medium for providing intervention in overcoming children's shyness.